Worker visibility and firms' retention policies - Simon Dato; Andreas Grunewald; Matthias Kräkel (Journal of Economics & Management Strategy, 2021)
In the last two decades, the widespread use of web-based social networks has led to a higher visibility of workers to the labor market. We theoretically and experimentally analyze the consequences of such increased labor market transparency for the efficiency of job assignments, the wages of workers, and firm profits. Our theoretical results show that higher visibility of workers increases the efficiency of job assignments, leads to a redistribution of income between workers of different ability, and increases overall surplus. Our experimental findings generally support the theoretical results with the exception that increased visibility leads to higher worker turnover such that surplus does not increase.
Keywords: 330